Influence of the addition of different ingredients on the bioaccessibility of glucose released from rice during dynamic in vitro gastrointestinal digestion. (2nd January 2021) - Fernandes, Jean-Michel; Madalena, Daniel Alexandre; Vicente, António Augusto; Pinheiro, Ana Cristina
Abstract: Rice represents a primary source of carbohydrates in human nutrition. Upon its consumption, the released sugars are mostly absorbed, categorising rice as a high glycemic index food. Addition of ingredients is common practice when cooking rice, which may affect rice digestibility and influence nutrients absorption in the gastrointestinal (GI) tract, enabling a controlled glucose release. In this sense, rice formulations were submitted to a dynamic in vitro GI model, constituted by reactors that simulates peristalsis coupled to filtration membranes, to evaluate carbohydrates hydrolysis and bioaccessibility. Addition of quinoa and wholegrains reduced carbohydrates hydrolysis (i.e. 38.5 ± 5.08% and 57.98 ± 1.91%, respectively) and glucose bioaccessibility (i.e. 25.92 ± 5.70% and 42.56 ± 1.39%, respectively) when compared with brown rice (i.e. 63.86 ± 2.96% hydrolysed and 44.33 ± 1.88% absorbed). Addition of vegetables significantly decreased sample chewiness and resulted in superior hydrolysis (71.75 ± 7.44%) and glucose absorption (51.61 ± 6.25%).